Communication's forgotten narratives: the lost history of Charles Siepmann and critical policy research. Issue 4 (7th August 2016) - Pickard, Victor
ABSTRACT: The field of communication has much to recover from its intellectual history, particularly critical traditions that have been pushed to the margins. Such a project is inherently political: how scholars narrate the histories of their fields reflect tacit assumptions about discursive boundaries and what counts for legitimate scholarship. Prominent historical narratives typically emphasize certain sub-fields and research traditions while giving short shrift to others. Suggesting larger erasures and deeper tensions in the history of the field, this article aims to recover one such neglected thread, embodied by a reformist policy scholar who is all but forgotten in communication research: Charles Siepmann.